2018
DOI: 10.3389/fpsyg.2018.00507
|View full text |Cite
|
Sign up to set email alerts
|

Eyewitness Memory in Face-to-Face and Immersive Avatar-to-Avatar Contexts

Abstract: Technological advances offer possibilities for innovation in the way eyewitness testimony is elicited. Typically, this occurs face-to-face. We investigated whether a virtual environment, where interviewer and eyewitness communicate as avatars, might confer advantages by attenuating the social and situational demands of a face-to-face interview, releasing more cognitive resources for invoking episodic retrieval mode. In conditions of intentional encoding, eyewitnesses were interviewed 48 h later, either face-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 90 publications
(108 reference statements)
2
24
0
Order By: Relevance
“…Witnesses were more accurate in their recall when questions were delivered socially rather than online. This increase in accuracy was not accompanied by a reduction in informativeness, indicating that other processes, such as increased motivation and feelings of accountability, were involved [e.g., McCallum et al, 2016; Vandierendonck & Van Damme, 1988; but see Taylor & Dando, 2018]. That the social condition improved accuracy rates similarly for autistic and TD witnesses is in contrast to the view that autism is marked by diminished social motivation [Chevallier et al, 2012] and is more in line with recent suggestions that autistic people are socially motivated, but that social‐cognitive difficulties can limit their ability to read and respond appropriately to social cues [see e.g., Hull et al, 2017; Jaswal & Akhtar, 2018; Livingston, Shah, & Happé, 2018].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Witnesses were more accurate in their recall when questions were delivered socially rather than online. This increase in accuracy was not accompanied by a reduction in informativeness, indicating that other processes, such as increased motivation and feelings of accountability, were involved [e.g., McCallum et al, 2016; Vandierendonck & Van Damme, 1988; but see Taylor & Dando, 2018]. That the social condition improved accuracy rates similarly for autistic and TD witnesses is in contrast to the view that autism is marked by diminished social motivation [Chevallier et al, 2012] and is more in line with recent suggestions that autistic people are socially motivated, but that social‐cognitive difficulties can limit their ability to read and respond appropriately to social cues [see e.g., Hull et al, 2017; Jaswal & Akhtar, 2018; Livingston, Shah, & Happé, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…This tendency is attenuated, however, when they are required to read their responses aloud to the experimenter compared to when their responses are obtained in private [McCallum et al, 2016]. It has been suggested that answering in a social context may motivate TD participants to be more accurate to avoid embarrassment by reporting more accurate CG detail than risk providing inaccurate FG information [McCallum et al, 2016; but see Taylor & Dando, 2018]. Furthermore, McCallum, Brewer, and Weber [2019] argue that witnesses construe informativeness based not only on the degree of specificity in their memories but also on their perceptions of the value or utility of the information.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we could predict that face‐to‐face interaction would be detrimental to witnesses' memory performance during investigative interviews. Whereas research has explored the effectiveness of interviews conducted without a physically‐present interviewer (Gabbert, Hope, & Fisher, 2009; Gawrylowicz, Memon, & Scoboria, 2014; Nash et al, 2014; Taylor & Dando, 2018), in current investigative practice at least one other person would normally be present with the witness during an interview.…”
Section: Introductionmentioning
confidence: 99%
“…As the digital world has expanded, multiple avatar subtypes have emerged, each with different, but related characteristics, dependent on avatar purpose such as therapeutic agent [4], and interview facilitation [5]. Of these, the social avatar is considered to be relatively informal, with high levels of user choice and control, a high degree of curation, and a predominantly positive skew (Table 1).…”
Section: Social Avatar Theorymentioning
confidence: 99%